Nano-NiFe2O4 as an efficient catalyst for regio- and chemoselective transfer hydrogenation of olefins/alkynes and dehydrogenation of alcohols under Pd-/Ru-free conditions. Issue 57 (1st June 2016) - Payra, Soumen; Saha, Arijit; Banerjee, Subhash
Abstract : Here, we have demonstrated magnetic nano-NiFe2 O4 catalyzed transfer hydrogenation of olefins/alkynes using isopropyl alcohol as source of hydrogen under ligand and Ru/Pd-free conditions and dehydrogenation of alcohols under oxidant-free conditions. Abstract : Here, we have demonstrated the magnetic nano-NiFe2 O4 catalyzed transfer hydrogenation of olefins/alkynes using isopropyl alcohol as a source of hydrogen under ligand/base/Pd-/Ru-metal-free conditions, and dehydrogenation of alcohols under oxidant-free conditions.